Outcome following use of the Achillon jig for the repair of acutely ruptured Achilles tendons. Issue 3 (March 2017) - Davies, Howard; Agrawal, Yuvraj; Blundell, Chris; Davies, Mark B.
Abstract: We report a series of 143 patients who underwent limited open Achilles tendon repair using the Achillon device at a mean follow-up of 25 months. All patients attending our institution with a diagnosis of acute Achilles tendon rupture were considered for operative repair using the Achillon jig unless they declined surgery or met the exclusion criteria. Following surgery patients were contacted and asked to complete an Achilles Tendon Rupture Score (ATRS). The clinical records were reviewed for evidence of complications, demographic information and evidence of re-rupture. Statistical analysis of subgroups including age at presentation, delay to surgery and patients with complications was carried out using the Kruskal Wallis non-parametric test. We report no re-ruptures at a mean of 25 months (minimum 12 months) following surgery. The mean ATRS score was 84/100 (range 15–100). There was no statistical significance between any of the subgroups analyzed. In conclusion, acute Achilles repair using the Achillon jig is safe, with a low re-rupture rate, excellent ATRS scores at a minimum of 12 months post-operatively and low complications. The incidence of sural nerve injury is much lower than published series of percutaneous Achilles tendon repair without the use of a jig.